Antifungal immunity mediated by C-type lectin receptors may be a novel target in immunotherapy for urothelial bladder cancer - Li, Tianhang; Liu, Tianyao; Zhao, Zihan; Pan, Yuchen; Xu, Xinyan; Zhang, Yulin; Zhan, Shoubin; Zhou, Shengkai; Zhu, Wenjie; Guo, Hongqian; Yang, Rong (Frontiers in Immunology, 2022)
Immunotherapy, such as immune-checkpoint blockade and adoptive T-cell therapy, has become novel treatment options with good efficacy for the patients with urothelial bladder cancer. However, the huge individual heterogeneity and therapeutic resistance largely limited the application of immunotherapy. Deeper understanding and research into the immune-regulatory mechanisms in bladder cancer are urgently required. Emerging evidence have recently demonstrated that commensal microbiota along with its interactions with host immunity played pivotal roles in a variety of physiological and pathological processes, including cancer. Gut microbiota has been identified as a potential effective target for synergizing immunotherapy. Urothelial tract is also a key residing site for multiple microbes. While the role of urinary microbiome and its immune-regulatory roles in the process of carcinogenesis of bladder cancer remains to be elucidated. Here in this hypothesis and theory article, we performed a comprehensive analysis on the expression and biological functions of C-type lectin receptors (CLRs), which have been recognized as innate pathogen-associated receptors for fungal microbiota, in bladder cancer. Under the premise of the previous verification of existence of colonization of fungi in the urothelial tract, we found members of CLRs, including Dectin-1, Dectin-2, Dectin-3 and Mincle, demonstrated a significant association with the immune infiltration in bladder cancer. Multiple innate and adaptive pathways are positively correlated with the up-regulation of the CLRs. In addition, we also found a significant correlation between the expression of CLRs and a range of immune-checkpoint proteins in bladder cancer. Based on previous relevant studies and our findings, we hypothesized that urinary mycobiome played a key role in the pathogenesis of bladder cancer and called for more research on CLR-mediated antifungal immunity against bladder cancer as a novel target for immunotherapy in urothelial bladder cancer.